MEMIKIRKAN MODEL PENDIDIKAN LITERASI BERBASIS KESURABAYAAN UNTUK TAMAN BACA MASYARAKAT (TBM) DI SURABAYA - Kukuh Yudha Karnanta, S.S., M.A (Universitas Airlangga, 2021)
This community service program aims to develop a creative writing model based on Surabaya’s local values. Surabaya’s local values refer to identity and common worldview of ‘arek Suroboyo’ such as egalitarianism, urban, and multicultural. Those values are tied in the main theme a revitalization of Surabaya Identity. Participants are 115 junior high schools in Surabaya. The community service program is conducted through student-centered learning, while the strategies are discovery learning and project-based learning using inquiry technique. Learning materials are collected from archives such as photos, videos, and field trips to certain places. This community service program give a significant contribution to cultivating a cultural understanding of the Surabaya, as exposed in participants' literary works.